Bioactivity assessment of the Saudi Arabian Marine Streptomyces sp. Al-Dhabi-90, metabolic profiling and its in vitro inhibitory property against multidrug resistant and extended-spectrum beta-lactamase clinical bacterial pathogens - Naif Abdullah Al-Dhabi; Abdul-Kareem Mohammed Ghilan; Galal Ali Esmail; Mariadhas Valan Arasu; Veeramuthu Duraipandiyan; Karuppiah Ponmurugan (Elsevier, 2019)
Background: Metabolites obtained from the marine microorganisms were known for their important role in microbial inhibition. Interestingly, bioprospecting of secondary metabolites from marine derived actinomycetes has huge demand especially in the treatment of multi drug resistant clinical pathogens. The present study subjected towards the identification of promising antimicrobial actinomycetes from the Arabian Gulf regions and metabolic profiling of the crude organic solvent extract by chromatographic techniques. Methods: The strains were characterized by 16S rRNA sequencing. Extracellular metabolites were profiled by performing GC-MS analysis. MIC values of the compounds were detected using broth dilution technique. Results: A Gram positive, spore forming filamentous Streptomyces sp. Al-Dhabi-90 possessed good antibacterial activities against the drug resistant pathogens were confirmed by 16S rRNA gene sequencing. Further, the gas chromatography coupled with mass spectrum analysis data revealed that the organic solvent extract of the fermented Streptomyces sp. Al-Dhabi-90 contained major components such as 3-methylpyridazine, n-hexadecanoic acid, indazol-4-one, octadecanoic acid and 3a-methyl-6-((4-methylphenyl) sul respectively. The Minimum Inhibitory Concentration (MIC) of the extract against Staphylococcus aureus and Klebsiella pneumoniae were 12.5 and 50 μg/ml respectively. Against drug resistant ESBL pathogens such as Escherichia coli, Pseudomonsa aeroginosa and Proteus mirabilis were 12.5, and 25 μg/ml respectively. Interestingly, the extract showed promising activity against the vancomycin resistant Enterococcus faecium at 50 μg/ml. The increased level of cellular constituents after the extract treatment evidenced that the metabolites altered the membrane integrity of the pathogens. Conclusion: Conclusively, the marine Streptomyces sp. Al-Dhabi-90 is an ideal source for the treatment of multi drug resistant clinical pathogens. Keywords: Streptomyces sp. Al-Dhabi-90, GC-MS, Multi drug resistant strains, Antibacterial activity, MIC